Determining the postmortem timing of sharp force damage and the pre-burning condition of burnt bone - Végh, Emese I.; Márquez-Grant, Nicholas; Schulting, Rick J. (Springer, 2024)
Major complications in the palaeopathological analysis of burnt human remains include distinguishing whether bone was fresh or dry at the time of burning, and whether trauma/damage was inflicted ‘perimortem’ or postmortem. Some prehistoric societies are suggested to have defleshed human remains prior to cremation, mostly classified based on the lack of warping and thumbnail fractures. The distinction between perimortem and postmortem sharp force trauma (SFT) characteristics has rarely been investigated on burnt bones. This study investigates whether these features are distinguishable on burnt bone, as well as assessing the rate of cutmark survival, and the presence of heat-induced fractures in relation to the bone’s pre-burnt collagen content. Pig (Sus scrofa domesticus) tibiae were left to decay in a field for 14, 34, 91, 180, and 365 days in Wytham Woods, Oxfordshire, UK. Prior to burning, bones were inflicted with SFT by a non-serrated and partially serrated knife and a flint blade (N = 15/bone). Fleshed bones with cutmarks and bones without trauma served as controls. Cutmark survival, features, and heat-induced fractures were recorded on the burnt bones and compared with the collagen extracted from unburnt bones at the abovementioned time intervals. Statistical analysis included linear regression and MANOVA. Heat-induced fractures did not depend on the limited collagen loss during the 1-year postmortem inverval (PMI) prior to burning. There was a loss (mean 18.4%) of identifiable cutmarks after burning. Significant alterations in the cutmark characteristics appeared after 6 months of exposure in burnt bones, marked by the increase in postmortem features, which can inform on the pre-burning PMI.
Keywords: Sharp-force trauma; Burning; Taphonomy; Perimortem; Human remains; Cremation